Revisional notes on Sericini: The taxonomic status of the ’Neotropical’ genus Rhynchosymmela Frey, 1974 (Coleoptera, Scarabaeidae). - Ahrens, Dirk (Contributions to Entomology = Beiträge zur Entomologie, 2004)
Based on an examination of the holotype, Rhynchosymmela pallida Frey, 1974 is recognized as a junior synonym of Hemiserica nasuta Brenske, 1894. The type locality of Rhynchosymmela pallida Frey is suspected to be erroneous. Important morphological characters of the holotype of Rhynchosymmela pallida Frey are figured and the distribution of Hemiserica, as well as that of Hemiserica nasuta, is mapped. Keywords Coleoptera, Scarabaeidae, Hemiserica, Rhynchosymmela, erroneous type locality, new synonymy, India, Panama. Nomenclatural Acts pallida Frey, 1974 (Rhynchosymmela), syn. n. of Hemiserica nasuta Brenske, 1894 Rhynchosymmela Frey, 1974 (Scarabaeidae), syn. n. of Hemiserica Brenske, 1894